PENGARUH KONFORMITAS TERHADAP AGRESIVITAS PENGGUNA APLIKASI WATTPAD - Valentino, David; Wullur, Mozes M.; Kapahang, Gloridei L. (PSIKOPEDIA, 2024)
This study aims to find the effect of conformity on aggressiveness in wattpad application users. This research uses a quantitative approach. The sample of this study were 100 members of wattpad lovers on facebook aged 16 years to 31 years and domiciled in various places, including Manado, Tomohon, Tondano, and Bekasi. This sample was selected using purposive sampling technique. In this study using two scales, namely, the aggressiveness scale from Buss and Perry (1992) modified by the researcher and the conformity scale made by the researcher based on the dimensions of Baron and Byrne (2005). Hypothesis testing was carried out using simple linear regression techniques and analyzed using IBM SPSS Statistic 24. The results of the analysis of this study indicate that conformity has an influence of 64.8% (p = 0.000; p < 0.05) on the aggressiveness of wattpad application users. The direction of influence is positive, which means that the higher the conformity, the higher the aggressiveness and vice versa, if the conformity is low, the aggressiveness will also be low.